2007
DOI: 10.1163/156855507782401132
|View full text |Cite
|
Sign up to set email alerts
|

Studies on thermal degradation of oligo-2-[(4-morpholin-4-yl-phenyl)imino methyl] phenol and oligomer–metal complex compounds

Abstract: Abstract-Thermogravimetric studies of 2-[(4-morpholin-4-yl-phenyl) imino methyl]phenol (2-MPIMP), oligo-2-[(4-morpholin-4-yl-phenyl) imino methyl] phenol (O-2-MPIMP) and its oli-gomer-metal complex compounds were investigated by thermal analysis. Four kinetic methods were used to investigate the thermal decomposition of these materials. These investigated methods are those of Coats and Redfern (CR), MacCallum and Tanner (MC), van Krevelen (vK) and Madhusudanan, Krishnan and Ninan (MKN). The values of the appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The thermal decomposition behaviours of some oligomer–metal complexes were studied by El‐Shekeil et al 15 and Kaya and Bilici 16. Doǧan and Kaya have investigated the thermal behaviour, kinetic and thermodynamic parameters of Schiff base oligomer–metal complexes using different methods based on a single heating rate in a nitrogen atmosphere with thermogravimetry (TG)/dynamic thermogravimetry (DTG) and DTA 17…”
Section: Introductionmentioning
confidence: 99%
“…The thermal decomposition behaviours of some oligomer–metal complexes were studied by El‐Shekeil et al 15 and Kaya and Bilici 16. Doǧan and Kaya have investigated the thermal behaviour, kinetic and thermodynamic parameters of Schiff base oligomer–metal complexes using different methods based on a single heating rate in a nitrogen atmosphere with thermogravimetry (TG)/dynamic thermogravimetry (DTG) and DTA 17…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we reported that the thermal stabilities of N, N ′‐bis(3,5‐di‐ t ‐butylsalicylideneimine)‐1,3‐propanediamine complexes of cobalt, nickel, iron, and copper increased in the following sequence: Ni(II) > Cu(II) > Co(II) > Fe(II) 22. Then, in another study, we determined that the thermal stabilities of the metal complexes of the oligo‐2‐[(4‐morpholin‐4‐yl‐phenyl)imino]methylphenol were in the following sequence: Cu(II) > Co(II) > Zn(II) > Zr(II) > Pb(II) > Cd(II) 10. As expected, these results clearly show that the thermal stabilities of the complexes increased as the ionic radii decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Copper(II)‐chelated polyazomethines were synthesized, and the influence of the copper content on the thermal behavior was studied by Oriol et al6 Thermally stable Schiff‐base polymers and their metal(II) complexes were reported by Mart 7. Schiff‐base substitute oligo/polyphenol–metal complexes and their thermal properties were examined by Kaya and coworkers 8–10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly believed that a single dynamic curve is equivalent to a large number of comparable isothermal curves and the theories developed for estimating isothermal reaction rate kinetic parameters can be applied to nonisothermal data. Thermogravimetry is a powerful tool to characterize the kinetic behavior of polymers . Doğan et al has been investigated the thermal behavior of azomethine‐based phenol polymer using different kinetic methods in a nitrogen atmosphere by thermogravimetric/derivative thermogravimetric analysis (DTG) and DTA.…”
Section: Introductionmentioning
confidence: 99%